Evaluation of patient satisfaction and the color difference between natural teeth and all-ceramic crowns fabricated from "Celtra press" treated with different surface finishing protocols. (Randomized controlled clinical trial) - Ahmed, Nourhan Sayed Saleh; Zamzam, Mohamed Labib; Taymour, Maha; Mohamed, Karim Abo Bakr (Journal of medical and pharmaceutical sciences, 2021)
All studies agree that glazing can produce a smooth porcelain surface, but although the glaze is an important factor in esthetics, with respect to light reflection, it can frequently change the color value of the restorations, reflecting more light than the natural teeth, thus creating an artificial effect on these restorations. A number of more recent studies have suggested that a polished surface may be as acceptable as a glazed surface. Many ceramists prefer polishing instead of glazing to control the surface luster. Other studies have reported no significant differences between polished and glazed surfaces.Since studies addressing the effect of surface finishing protocols on the color of ZLS ceramics are rare, thus our study is important to investigate this issue.Methodology: 20 teeth esthetic zone requiring full - coverage crown -with their contralateral are sound and not severely discolored - were prepared to receive an all -ceramic crown. The crowns are divided into two groups: Group I: Teeth received crowns fabricated from glazed Celtra Press ceramic Group II: Teeth received crowns fabricated from polished Celtra Press. The color difference ΔE was measured using an intraoral spectrophotometer and evaluated for each group. Shade matching to the contralateral tooth was evaluated by 2 experienced prosthodontists according (USPHS) criteria. Patient satisfaction of the two groups assessed using the (VAS) scale which is Binary and documented in the chart.Results: Patient satisfaction was graded according to the (VAS) scale. There was no statistically significant difference between (Group I) and (Group II). The color change was recorded according to the (ΔE), the polished Celtra Press group recorded statistically non-significant higher color changes than the glazed Celtra Press group. shade matching was graded according to USPHS, where in Glazed Celtra Press group most of the patients stated Alpha score (80%) while minority showed Bravo score (20%). In the Polished Celtra Press group, all of the patients informed Bravo score100%.Conclusion: Within the limitations of this clinical study:Glazed and polished Celtra Press full coverage restorations revealed excellent patient satisfaction. Glazed celtra restorations have a clinically more acceptable shade matching.
Keywords: celtra; celtra press; glazing; ceramics; polishing; esthetics